Evaluation of Financial Performance in Applying Regional Autonomy in Regional Government Of Majalengka Regency - Ligar Hardika, Andhika; Haizam Saudi, Mohd; Surayya Saudi, Nur (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze and evaluate the assessment of regional financial performance in the accountability and transparency of the financial statements of the Regional Budget (APBD) as a result of decentralization or regional autonomy. Regional monetary management is one aspect of the implementation of regional autonomy that is carried out effectively and efficiently so that the realization of civil society welfare. The research sample is financial data in the form of regional cost sources and regional revenue budgets as well as regional expenditure allocations in 2013- 2018 in the Regional Government of the Majalengka Regency, West Java. The result of this research is that the financial performance of the Majalengka Regency district needs to increase the contribution of taxes and levies to support the Locally Generated Revenue while the need for effective and efficient use of SILPA. Another analysis of independence, the effectiveness of Locally Generated Revenue and local taxes as well as efficient and harmonious spending was obtained that the Regional Government of the Majalengka District was quite good despite fluctuations, so it was necessary to increase financial resources and use them more optimally so that public facilities were met.